PERAWAN GATRA: Innovation in Public Services at The Local Police Unit - Muhammad Hudan Fathanudin; Siti Khumayah (Sahabat Publikasi, 2026)
PERAWAN GATRA (Peta Rawan Gangguan Ketenteraman dan Ketertiban Umum) or Map of Areas Prone to Disturbances of Public Peace and Order is a service innovation by the Cirebon City Civil Service Police Unit (Satpol PP), based on geospatial data to identify areas prone to disturbances of public peace and order that are accessible to the public. This study focuses on the quality of public service innovations that can create value and are recognized and supported by the community. It employs the Public Value theory (Mark H. Moore, 1995), which focuses on the dimensions of public value that are recognized and supported by the community. The research method used is qualitative, with data sources including observation, interviews, and documentation. Based on the research findings, the PERAWAN GATRA innovation successfully creates public value regarding public trust through four dimensions: 1) Public Value, where the public gains easier access to digital information; 2) Community-Driven Innovation, as PERAWAN GATRA serves as a solution and simplifies information access for the public regarding public order disturbances; 3) Public Legitimacy and Support, as public trust increases with the availability of transparent geospatial-based digital data in addressing public order disturbances; and 4) Organizational Operational Capacity, which involves forming a team for processing geospatial-based digital data within the PERAWAN GATRA innovation. Challenges include infrastructure, servers, devices, outreach, and digital literacy. Efforts undertaken include outreach through digital media, collaboration with government agencies, and training for staff members. Overall, PERAWAN GATRA demonstrates a positive contribution and holds public value for digital public service innovation, although further evaluation is needed to achieve optimal quality.